Proposed new interior design scheme of production house office at Lot 1A, 1B & 2, Block P1, Lorong Selangor, Gaya @ Melawati Urban 2, Taman Melawati 53100 Gombak, Selangor for CST Production / Siti Nuradibah Mohd Nordin - Mohd Nordin, Siti Nuradibah (Faculty of Architecture, Planning and Surveying, 2012)
This report documentating the design process of the proposed new interior design of production house for CST Production. The proceedings are conducted by various ways of data collection. This report is a compilation of what researcher have to do to get an outcome based on the guidelines. This report is also to compile all data and information obtained throught out the process about the project, site and design. Many kind of process were undergone before completing the whole compilation about the project. By completing writing about the whole procedure, this project can be understood and comprehends by readers. At the end of this documentation, the problem statements and issues of this project would be solved using all data collected throught out the whole proceedings. The design proposal would be shown in complete proposal scheme.